Когерентні зв’язки основних ритмів ЕЕГ головного мозку правшів та лівшів при монокулярному сприйнятті домінантним чи недомінантним оком вербальної емоційної інформації - Бондаренко (Рассомагіна), Марія; Кравченко, Вікторія; Макарчук, Микола; Bondarenko (Rassomagina), Maria; Kravchenko, Viktoriya; Makarchuk, Mukola (Східноєвропейський Національний університет імені Лесі Українки, 2015)
Проведено порівняльну оцінку когерентних зв’язків основних ритмів ЕЕГ у 60 обстежуваних (30 лівшів з домінантним лівим оком та 30 правшів з домінантним правим оком) при монокулярному виконанні Струп- тесту за умов пред’явлення емоційно значущих слів чи псевдослів. The comparative estimation of coherent connections of the main EEG rhythms in 60 subjects (30 left-handers with left dominant eye and 30 right-handers with right dominant eye) was performed using Stroop-test with emotional words and meaningless words. During monocular vision of emotional words and meaningless words changes of coherence only within one hemisphere was observed, so under these conditions interhemispheric interactions are deteriorated. Monocular recognition of the color of the emotional words accompanied by coherence changes in both hemispheres of the brain, the most pronounced in left-handers. Instead, performance of the similar tasks with meaningless words leads to a decrease of the coherence connections in the contralateral (to the opened eye) hemisphere in right-handers and left-handers. Task with meaningless words causes less influence on the relevant brain structures than the task with emotional words, as evidenced by the reduction of coherent connections during the test with meaningless words.
Сoherent Connections of the Basic EEG Rhythms in Right-handers and Left-handers During Monocular Perception of Verbal Emotional Information Through Dominant and Non Dominant Eye.
Keywords: Струп-тест; домінантне око; недомінантне око; монокулярний зір; емоційні вербальні стимули; когерентність; Stroop-test; dominant eye; nondominant eye; monocular vision; emotional verbal stimuli; coherence